Analysis of Genetic Alteration Signatures and Prognostic Values of m6A Regulatory Genes in Head and Neck Squamous Cell Carcinoma - Zhou, Xuanchen; Han, Jie; Zhen, Xiaoyue; Liu, Yiqing; Cui, Zhaoyang; Yue, Zhiyong; Ding, Ling; Xu, Shuai (Frontiers in Oncology, 2020)
Genetic alteration involving N6-methyladenosine (m6A) regulatory genes are a frequent characteristic of multiple tumors. Nevertheless, little is known regarding their genetic alteration signatures and prognostic values in head and neck squamous cell carcinoma (HNSCC). In this study, RNA sequence profiles and copy number variation (CNV) data of 506 HNSCC patients were downloaded from The Cancer Genome Atlas (TCGA) database. Correlation analysis involving alteration of m6A regulatory genes, clinicopathological characteristics, and patient survival was performed using R language. The results suggested that alteration of m6A regulatory genes was correlated with clinical staging. Patients with high expression of ALKBH5, FTO, METTL14, WTAP, YTHDC1, YTHDF1, and YTHDF2 had poor overall survival (OS) than those with low expression. Univariate and multivariate Cox regression analyses showed that ALKBH5 and YTHDC2 were independent risk factors for OS. However, patients with high YTHDC2 expression had a better OS. Moreover, according to machine learning results, YTHDC2 was found to be the most important gene among the ten m6A regulators. Additionally, high expression of YTHDC2 was correlated with activation of apoptosis and ubiquitin-mediated proteolysis. Here, we identified alterations to m6A regulatory genes in HNSCC for the first time and found that seven m6A regulators were associated with poor prognosis, especially ALKBH5,whereas YTHDC2 was associated with better prognosis. These m6A-related regulators could act as novel prognostic biomarkers for HNSCC. Our findings provide clues for understanding RNA epigenetic modifications in HNSCC.